Solving the restructuring problems of (former) old industrial regions with smart specialization? Conceptual thoughts and evidence from the Ruhr - Robert Hassink; Matthias Kiese (Review of Regional Research, 2021)
(Former) old industrial regions are a~specific kind of lagging regions that suffer from long-term restructuring problems and deindustrialization. They are back in the focus of many researchers as well as media observers, because of the rise of populist parties in many of these regions in North America and Europe. Therefore, new policy options are discussed in the literature. In this paper, we critically discuss the effects of smart specialization as the most recent regional policy strategy in Europe on solving the restructuring problems and deindustrialization in (former) old industrial regions and we illustrate our analysis with a~view on the Ruhr in Germany. Since smart specialization focuses on existing endogenous potential and entrepreneurial discovery processes from the region, vested interests in (former) old industrial regions might hinder necessary restructuring. Although potentially path transformation might be fostered in some cases, overall, smart specialization is certainly not a~quick fix for solving long-term negative effects of restructuring and deindustrialization in (former) old industrial regions.
Keywords: R10; 910; Lagging regions; (Former) old industrial regions; Smart specialization; The Ruhr